A Bánság földrajzos szemmel - Pál, Ágnes (Közép-Európai Közlemények, 2010)
This survey is to offer a brief insight into the past and the present of Bánság, a region, which used to represent a highly valued social, economic and cultural area in the Carpathian Basin. On the other hand we do not undertake the task of offering a historical analy sis, since historical considerations belong to the realm of historians. Instead, starting from the very roots, we intend to outline the present, and, possibly some future chracteristics of the region from the perspective of geography. This point of view is also justified by the fact that one part of the region lies in Temes County, Romania, and the other one in Voivodina, Serbia. By taking this region as an example, we also aim at describing the significance of present day's regions in general, and also at outlining some theoretical issues, which are related to regional development.